The Effectiveness of Role-Play Integrated with Word Cards on Students’ Speaking Skill for Communication - Bagus Putra Krisdiana; Enny Irawati; A. Effendi Kadarisman (Pascasarjana UM, 2018)
Abstract: This study aims to investigate the effectiveness of role play integrated with word cards on students’ speaking skill for communication. A one group pretest-posttest design with the 23 students were given treatments for six meetings. To achieve the aim of the study, a pretest before the treatment, and posttest, after the treatment, are constructed. Then, the mean scores of both tests are compared. It is found that the mean score in the posttest is significantly higher than in the pretest. It means role-play integrated with word cards is effective in improving students’ speaking skill for communication.Key Words: role-play, word cards, speaking skill, communication, effectiveAbstrak: Penelitian ini bertujun untuk meneliti keefektifan bermain peran yang digabungkan dengan kartu kata terhadap keterampilan berbicara siswa untuk berkomunikasi. Rancangan penelitian mengguna-kan tes awal - tes akhir satu kelompok dengan 23 siswa diberi perlakuan selama enam pertemuan. Untuk mencapai tujuan dari penelitian ini, tes awal, sebelum perlakuan, dan tes akhir, setelah perlakuan, diberikan. Kemudian, nilai rata-rata kedua tes dibandingkan. Ditemukan bahwa nilai rata-rata dari tes akhir lebih tinggi secara signifikan daripada tes awal. Artinya bahwa bermain peran yang digabungkan dengan kartu kata efektif dalam meningkatkan keterampilan berbicara untuk berkomunikasi. Kata kunci: bermain-peran, kartu kata, kemampuan berbicara, komunikasi, efektif